FROM THE NATIONAL EVALUATION POLICY FOR EARLY CHILDHOOD EDUCATION TO EVALUATION IN PEDAGOGICAL PRACTICE (Editora Impacto Científico, 2025)
With the enactment of LDBEN (Law No. 9.394/96), Early Childhood Education officially became part of Basic Education and was included in the field of public education policies. The research highlights that although this stage has expanded in terms of access, the challenge of quality still persists, requiring parameters and indicators to guide evaluation practices that are coherent with the EI context. The study, with a qualitative approach and based on Mainardes and Marcondes' policy cycle, analyzes legal and normative documents that guide evaluation in and of Early Childhood Education, seeking to identify, among other aspects, the influence of the Reggio Emilia approach.Early childhood education assessment remains permeated by tensions between different conceptions: while some approaches prioritize the conditions of provision, others focus on children's performance. These differences reflect disputes over values and have a direct impact on teaching practices, the curriculum and the relationships established in everyday school life. The study reinforces the importance of understanding that every evaluation carries positions and choices that are not neutral, demanding critical responsibility from the formulators and executors of public policies.